First experiments on plasma production using field-aligned ICRF fast wave antennas in the large helical device. (1st October 2021) - Kamio, S.; Moiseenko, V.E.; Kovtun, Yu.V.; Kasahara, H.; Saito, K.; Seki, R.; Kanda, M.; Nomura, G.; Seki, T.; Takemura, Y.; Wauters, T.; Brakel, R.; et al.
Abstract: The results of the first experimental series to produce a plasma using the ion cyclotron range of frequency (ICRF) in the large helical device (LHD) within the minority scenario developed at Uragan-2M (U-2M) are presented. The motivation of this study is to provide plasma creation in conditions when an electron cyclotron resonance heating start-up is not possible, and in this way widen the operational frame of helical machines. The major constraint of the experiments is the low RF power to reduce the possibility of arcing. No dangerous voltage increase at the radio-frequency (RF) system elements and no arcing has been detected. As a result, a low plasma density is obtained and the antenna-plasma coupling is not optimal. However, such plasmas are sufficient to be used as targets for further neutral beam injection (NBI) heating. This will open possibilities to explore new regimes of operation at LHD and Wendelstein 7-X (W7-X) stellarator. The successful RF plasma production in LHD in this experimental series stimulates the planning of further studies of ICRF plasma production aimed at increasing plasma density and temperature within the ICRF minority scenario as well as investigating the plasma prolongation by NBI heating.